EFFECTS OF PLANTING DENSITY AND CROPPING PATTERN ON THE DRY MATTER ACCUMULATION AND YIELD OF MAIZE (ZEA MAYS L.) IN SOUTHWEST CHINA - Q. Li; F. Kong; W. Long; Y. Wu; Q. Cheng; P. Dou; X. Ma; J. Yuan1; X. Guo (Journal of Animal and Plant Sciences, 2019)
Maize (Zea mays L.) is one of the most important cereal crops worldwide. However, the grain yield of maize has lagged even as its demand has increased with human population growth. Ecological conditions have significant effects on maize yield. For example, fertile soils could increase the dry matter accumulation of maize, and abundant light and temperature are the basis for high maize yields. Plant density and cropping pattern also exert important effects on the grain yield of cereal crops. This study investigated the growth characteristics, dry matter accumulation (DMA) and distribution, yield, and yield components of maize planted at different densities and with different cropping patterns. Field experiments were conducted in Shehong (SH), Shuangliu (SL), and Yaan (YA) in Southwest China in 2012. Zhenghong 6 was planted at densities of 37,500; 48,750; or 60,000 plants ha−1 in equal or wide-narrow rows with single or double plants per hole. Results showed distinct differences in ecological conditions at the three planting sites. Thus, the plant height, leaf area index (LAI), DMA, and yield of maize were significantly higher in SL than in SH and YA, and the lowest values for these parameters were observed in YA. With increasing plant density, the DMA of each plant decreased, whereas plant height, LAI, and DMA at the population level and yield markedly increased. The highest values for these parameters were consistently correlated with the highest plant density in all experimental sites. In addition, grain yield significantly changed with cropping pattern under limiting conditions. Overall, the results suggested that increasing plant density within a certain range under single and wide-narrow row cultivation is a feasible strategy to increase the grain yield of maize in Southwest China.
Keywords: maize; plant density; cropping pattern; dry matter; yield